ON NORMAL FERMI-WALKER DERIVATIVE FOR FOCAL CURVES WITH MODIFIED FRAME - Yeneroglu, Mustafa; Korpinar, Talat (Editura Bibliotheca-Bibliotheca Publ House, 2019)
In this paper, we study a new construction of curves by normal Fermi-Walker parallelism and derivative with modified frame. Finally, we give normal Fermi-Walker parallelism and derivative for a focal curve according to modified frame.
Keywords: Modified frame; normal Fermi Walker derivative-parallelism; Focal curve